Informal family insurance and the design of the welfare state - Rafael DiTella; Robert MacCulloch (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 1999)
We study the problem of unemployment benefit provision when the family is also a provider of social insurance. As a benchmark, a simple model is presented where risksharing motives govern intra-family transfers and more generous unemployment benefits, provided by the State, crowd out family risk-sharing arrangements one-forone. The model is then extended to capture the idea that the State has an advantage vis-a-vis the family in the provision of insurance because it can tax individuals, whereas the family must rely on self-enforcing agreements. In this case, the effect of State transfers on intra-family transfers is found to be more than one-for-one. Thus, somewhat perversely, both informal transfers and total insurance transfers to the unemployed fall as the State's generosity increases. This does not imply that the optimal Welfare State is zero. Our results still hold when families are assumed to be better than the State at monitoring the job search activities of the unemployed.
Keywords: H42; H53; D1; I38; 330; Self-enforcing contracts; Optimal welfare generosity; Sozialstaat; Arbeitslosenversicherung; Familie; Privater Transfer; Selbsthilfe; Crowding out